PERBANDINGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DAN ANALYCTICAL HIERARCHY PROCESS (AHP) DALAM MENENTUKAN REKOMENDASI SHUTTLECOCK BADMINTON TERBAIK - Suhardi Suhardi; Muhammad Siddik Hasibuan; Erwin Nasution; Ichsan Rafisyah (UIN Sumatera Utara Medan, 2021)
The choice of shuttlecock is very important in playing badminton. In determining the shuttlecock to play badminton generally only involves reasoning skills or choosing randomly. Determination of shutllecock recommendations is considered important because through this activity the quality of each brand can be known. The method used in the shuttlecock selection decision support system is using the Simple Additive Weight (SAW) and Analytic Hierarchy Process (AHP) methods which aim to compare SAW and AHP. The criteria used are feather material, cork material, speed, level of usage, and price. The decision support system is designed with the PHP programming language and MySQL database to test and determine the ranking of several available alternatives. Then the results obtained from the assessment using the SAW method as the main priority of Yonex Shuttlecock Aerosena 50 (code: S3) as the best shuttlecock, while with the AHP method the main priority was Shuttlecock Victore Master Ace (code: S13) as the best shuttlecock. The ranking of each method will be used as a consideration for badminton players in choosing the appropriate shuttlecock for use